2021
DOI: 10.1002/rth2.12496
|View full text |Cite
|
Sign up to set email alerts
|

Risk of thrombotic complications in influenza versus COVID‐19 hospitalized patients

Abstract: Background Whereas accumulating studies on COVID‐19 patients report high incidences of thrombotic complications, large studies on clinically relevant thrombosis in patients with other respiratory tract infections are lacking. How this high risk in COVID‐19 patients compares to those observed in hospitalized patients with other viral pneumonias such as influenza is unknown. Objectives To assess the incidence of venous and arterial thrombotic complications in hospitalized… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 32 publications
2
59
4
Order By: Relevance
“…Among hospitalised ##ward/inward## patients, a meta-analysis reported a pooled incidence of deep vein thrombosis and pulmonary embolism (assessed by screening or clinical diagnosis) of 7.1% (95% CI, 4.8–9.8) [5] . This incidence is higher than in non-COVID viral pneumonia: Elgendy et al reported an incidence of VTE of 1.0% among 455,629 hospitalised patients with a primary diagnosis of non-COVID-19 viral pneumonia [6] ; Stals et al reported a 30-day adjusted cumulative incidence for venous thrombotic complications of 3.6% (95% CI, 2.7–4.6) in influenza versus 23% (95%CI, 16–29) in COVID-19 hospitalised patients [7] .…”
Section: Methodsmentioning
confidence: 99%
“…Among hospitalised ##ward/inward## patients, a meta-analysis reported a pooled incidence of deep vein thrombosis and pulmonary embolism (assessed by screening or clinical diagnosis) of 7.1% (95% CI, 4.8–9.8) [5] . This incidence is higher than in non-COVID viral pneumonia: Elgendy et al reported an incidence of VTE of 1.0% among 455,629 hospitalised patients with a primary diagnosis of non-COVID-19 viral pneumonia [6] ; Stals et al reported a 30-day adjusted cumulative incidence for venous thrombotic complications of 3.6% (95% CI, 2.7–4.6) in influenza versus 23% (95%CI, 16–29) in COVID-19 hospitalised patients [7] .…”
Section: Methodsmentioning
confidence: 99%
“…Our ICU followed well-coordinated protocols in managing respiratory failure, making this more likely an effect of anticoagulation than chance observation. Stals et al reported a similar rate of SARS-CoV-2 infected patients on chronic anticoagulation requiring hospitalization at 13% [6] . They did not comment on whether there was a difference in disease severity.…”
mentioning
confidence: 91%
“…This may be explained by a more intensive inflammatory state and resultant coagulation activation, combined with complete immobilization and resultant lower limb paralysis during mechanical ventilation, and the frequent use of central venous catheters [40][41][42][43]. Moreover, the incidence of thrombotic complications in COVID-19 patients seems to be higher than reported in ICU patients hospitalized for other diseases including influenza [14,44]. Once the high incidence of thrombotic complications in hospitalized COVID-19 patients was elucidated, the threshold to suspect VTE and foremost PE among clinicians lowered.…”
Section: Evidence For Thrombotic Complications In Covid-19mentioning
confidence: 99%
“…Early studies from Wuhan (China) already reported on coagulation abnormalities and coagulopathy in hospitalized patients with COVID-19 at the beginning of 2019 [6][7][8]. This was followed by studies from Europe and America finding alarmingly high rates of VTE in patients with severe COVID-19 infection treated at Intensive Care Units (ICU) and wards [9][10][11][12][13][14][15]. Incidences in these studies varied, but cumulative inci-dences of nearly 50% were reported in ICU patients and, although lower, between 5% and 10% in COVID-19 patients hospitalized on the general wards [16][17][18].…”
Section: Introductionmentioning
confidence: 99%